The Assessment of the Influence of Risk Factors on Arterial Hypertension - Rajabova Dilafro‘z Bozorovna (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Arterial hypertension (AH) remains one of the most prevalent non-communicable diseases globally and a leading contributor to cardiovascular morbidity and mortality. Specific Background: Despite extensive research on individual determinants, little is known about the combined impact of behavioral, biological, and lifestyle factors in rural populations within specific sociocultural settings such as Uzbekistan. Knowledge Gap: Existing studies have largely focused on isolated risk factors, overlooking their synergistic effects and limited data from Central Asian populations undergoing rapid lifestyle transitions. Aims: This study aimed to assess the influence of major risk factors—including obesity, smoking, physical inactivity, and salt consumption—on the prevalence of arterial hypertension among adults in rural Uzbekistan. Results: A cross-sectional survey involving 6,644 adults revealed that 57.8% had at least one major risk factor. Obesity, overweight, genetic predisposition, and smoking were significant predictors with relative risks of 10, 8.3, 2.2, and 1.92, respectively. Hypertension prevalence was up to 4.5–5 times higher in overweight individuals. Novelty: The study provides the first comprehensive analysis of multiple concurrent risk factors for hypertension within a Central Asian context. Implications: These findings underscore the urgent need for community-based interventions focusing on weight control, physical activity, dietary modification, and smoking cessation to reduce hypertension prevalence and improve cardiovascular outcomes.Highlight : The study identifies obesity and overweight as the main determinants of arterial hypertension. It stresses lifestyle modification such as reducing smoking and increasing physical activity. The findings emphasize prevention and health education, especially in rural communities. Keywords : Arterial Hypertension, Risk Factors, Obesity, Smoking, Blood Pressure